Gegenwärtige vergangenheit : ausgewählte kleine schriften - Pöhlmann, Egert (Beiträge zur Altertumskunde, 2009)
Egert Phlmann held the Chair of Classical Studies at the University of Erlangen until 2001. His minor writings collected here cover the period from 1968 to 2008. As well as papers on Greek and Latin Studies and music in Antiquity, there is work seeking links between topics in Classical Studies and neighbouring disciplines such as Antique philosophy, archaeology, art history, modern German literature and music. The volume closes with a bibliography of Egert Phlmann's writings.